2020
DOI: 10.3389/fneur.2020.00703
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role of Astrocyte Connexin 43 in Ischemic Stroke Through Forming Hemichannels and Gap Junctions

Abstract: Ischemic stroke is a multi-factorial cerebrovascular disease with high worldwide morbidity and mortality. In the past few years, multiple studies have revealed the underlying mechanism of ischemia/reperfusion injury, including calcium overload, amino acid toxicity, oxidative stress, and inflammation. Connexin 43 (Cx43), the predominant connexin protein in astrocytes, has been recently proven to display non-substitutable roles in the pathology of ischemic stroke development and progression through forming gap j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 162 publications
(196 reference statements)
1
39
0
Order By: Relevance
“…It has been described that, early after an ischemic insult (1–30 min), Cx43 gap junctions are phosphorylated by several kinases, like MAPK, PKC, pp60Src, and casein kinase 1δ, which triggers internalization of Cx43 hexamers. The remaining Cx43 hemichannels are dephosphorylated in a subsequent stage (after 60 min), increasing their opening probability and allowing harmful molecules into the extracellular space (ECS), like ATP and glutamate [ 84 ]. Leptin was found to suppress Cx43 rise after I/R reducing brain damage in a mouse model of MCAO, and it also blocked Cx43 hemichannels in cultured U87 cells [ 85 ].…”
Section: Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been described that, early after an ischemic insult (1–30 min), Cx43 gap junctions are phosphorylated by several kinases, like MAPK, PKC, pp60Src, and casein kinase 1δ, which triggers internalization of Cx43 hexamers. The remaining Cx43 hemichannels are dephosphorylated in a subsequent stage (after 60 min), increasing their opening probability and allowing harmful molecules into the extracellular space (ECS), like ATP and glutamate [ 84 ]. Leptin was found to suppress Cx43 rise after I/R reducing brain damage in a mouse model of MCAO, and it also blocked Cx43 hemichannels in cultured U87 cells [ 85 ].…”
Section: Astrocytesmentioning
confidence: 99%
“…At higher exposure times Gap19 slightly inhibits gap junctions. Suppression of Cx43 by Gap19 showed beneficial effects in MCAO mouse models [ 84 ].…”
Section: Astrocytesmentioning
confidence: 99%
“…Cx43 is the primary component protein of connexin channels in brain tissue, and its enhanced expression can accelerate intercellular signal transduction, aggravating damage after injury. Studies have shown that hypoxia and inflammation synergistically accelerate the activity of Cx43 hemichannels under ischemic conditions (Faigle et al, 2008), leading to the loss of astrocytes and neuronal death (Liang et al, 2020). One study showed that 1 hour after TBI, the expression of phosphorylated Cx43 in the ipsilateral hippocampus was significantly induced and remained at a high level until 24 hours after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although Connexin (Cx) 26, Cx30, and Cx43 were shown to play a role in brain homeostasis, Cx43 is considered the main gap junction protein in astrocytes. A number of in vivo and in vitro studies, using pharmacological gap junction inhibition or the deletion or overexpression of Cx43, confirmed the relevance of Cx43 for astrocytic well-being [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 94%